"É sempre bom ter nosso dinheiro": sobre a mulher e o extrativismo da mangaba - FERNANDES, Thiara (Universidade Federal do Pará, 2021)
In this research is analyzed the woman autonomy in the Mangaba fruit (Hancornia speciosa) extraction in a farm work family regime, through the study of their everyday extraction activities and the use of their resources. Aiming that, I carried out a case study in a coastline in the north of Brazil, Pará‘s Salgado micro region in the municipality of Maracanã, Espírito Santo community. Academic researches point that in the farm work the woman activity is constantly subordinate to the man‘s, and it is understood as just a ―helping hand‖ even when they dedicate the same or more and obtain the same work results. Differently, researches about women work in the extraction activity suggest that they develop this work with autonomy, mainly the mangaba fruit pickers, the babaçu fruit breakers and the rubber tree tappers. The case study was held in the community with 15 families following direct observation, structured and semi structured interviews. Two aspects were analyzed: i) the woman productive and domestic work and ii) the income access and enjoyment conceived by her work. The main conclusions showed that, concerning to the farm work, different family arrangements are always associated to the domestic structure operation maintenance. About the resources conceived, the mangaba fruit harvest is the only season of the year that the farm work women can save a little ―savings‖ that is spent reasonably during the year, to possible eventualities, such as family diseases and acquisition of consumer goods. Besides, they use the resources to buy input to the animal husbandry. That way, mangaba fruit extraction, that is a seasonal activity, subsidizes the existence of further activities. Concerning to autonomy, 66% of women who are involved in the mangaba fruit extraction state their own autonomy in the work and in the income as well. In 33% of cases, they state themselves as subordinated to men.